2014
DOI: 10.4266/kjccm.2014.29.2.59
|View full text |Cite
|
Sign up to set email alerts
|

Severe Fever with Thrombocytopenia Syndrome

Abstract: Severe fever with thrombocytopenia syndrome (SFTS) is a newly emerging infectious disease, caused by a novel species of Phlebovirus of Bunyaviridae family, in China, South Korea, and Japan. SFTS is primarily known as a tick-borne disease, and human-to-human transmission is also possible in contact with infectious blood. Common clinical manifestations include fever, thrombocytopenia, and leukopenia as initial symptoms, and multiple organ dysfunction and failure manifest with disease progression. Whereas disease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…SFTSV also occurred in South Korea where the first clinically suspected patient was reported on Jeju Island in May 2013, followed by SFTSV isolation by Seoul National University Hospital in a retrospective study [ 15 18 ]. The Korean Center for Disease Control reported that until November 2013, there were 36 positives out of 404 suspected SFTSV cases, wherein 17 of 36 confirmed cases were fatal cases [ 19 ]. Epidemiological studies in these countries revealed that 90% of patients were older than 35 years of age (median age of 58 years) and most were farmers [ 19 ].…”
Section: Epidemiology and Vectors Of Sftsvmentioning
confidence: 99%
“…SFTSV also occurred in South Korea where the first clinically suspected patient was reported on Jeju Island in May 2013, followed by SFTSV isolation by Seoul National University Hospital in a retrospective study [ 15 18 ]. The Korean Center for Disease Control reported that until November 2013, there were 36 positives out of 404 suspected SFTSV cases, wherein 17 of 36 confirmed cases were fatal cases [ 19 ]. Epidemiological studies in these countries revealed that 90% of patients were older than 35 years of age (median age of 58 years) and most were farmers [ 19 ].…”
Section: Epidemiology and Vectors Of Sftsvmentioning
confidence: 99%
“…Since the first discovery of SFTSV in Hubei in China in 2010, the disease has rapidly spread to Fujian province which is only a strait away from Taiwan [1]. Later in 2012-2013, the first SFTS human case in Japan and South Korea were reported [5]. From 2013 to 2016, there were a total of 7419 confirmed human cases occurred in China with 355 deaths [1].…”
mentioning
confidence: 99%
“…There have been constant reports after the first patient was identified through the retrospective isolation of the virus in May 2013 [210]. Laboratory confirmation of SFTSV is established through the isolation of SFTSV in cell culture, viral identification through the RT-PCR or DH82 cells from the patient's serum, or serologic detection of 4-fold increase in anti-SFTS virus immunoglobulin G titers between acute and convalescent phases [6]. Laboratory diagnosis takes times so long from several days to weeks, even if RT-PCR takes approximately minimum 5-7 days to know the results from Korean Centers for Disease Control and Prevention.…”
Section: Discussionmentioning
confidence: 99%
“…It has been known that several cytokines (interleukin (IL)-1β, IL-8, macrophage inflammatory protein 1β, and interferon-gamma) are elevated in patients with SFTS, and the serum levels of cytokines are correlated with serum viral loads and disease severity. As a result, the cytokine-mediated inflammatory response may play an important role in the disease progression in patients with SFTS [569]. Based on this theory, several cases have reported that the plasma exchange were able to remove the immune complexes correlated with disease severity, such as cytokines, reduce serum cytokines, and improve the clinical courses in patients with ARDS or hemodynamic shock [1112].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation